'We are the teachers of the nation': A discursive analysis of institutional identity in Ghanaian University anthems - Antwi, Eric; Adogpa, James Nsoh; Abana, Mary Yibel (Humanities & Language: International Journal of Linguistics, Humanities, and Education, 2026)
This study investigates the anthems of two prominent Ghanaian universities, the University of Cape Coast (UCC) and the University of Education, Winneba (UEW), to understand how they contribute to institutional identity and serve as tools for institutional branding within a competitive higher education context. The study is informed by Social Identity Theory (Tajfel & Turner, 1979) and Institutional Branding Theory (Balmer & Gray, 2003). Utilising a qualitative multiple case study design, the study purposively selected official lyrics of anthems of both universities, conducting textual analysis complemented by thematic analysis. The findings indicate that UCC and UEW strategically leverage their anthems to project distinct brand identities to both internal and external audiences, with UCC foregrounding pedagogical leadership and national service, and UEW emphasising moral purpose and ethical excellence. Despite these contrasts, three core identity dimensions emerged for both institutions: professional teacher education, institutional pride and prestige, and forward-looking aspirations. The study concludes that university anthems serve as active instruments of identity construction and branding, reinforcing cohesion, distinctiveness, and the institutional mission. These findings underscore the importance of symbolic cultural artefacts in shaping the identity and communication strategies of higher education institutions.